Effect of parenterally l-arginine supplementation on the respiratory distress syndrome in preterm newborns. (17th July 2016) - Cansever, Murat; Akin, Mustafa Ali; Akcakus, Mustafa; Ozcan, Alper; Gunes, Tamer; Ozturk, Adnan; Kurtoglu, Selim
Abstract: l -Arginine (l -Arg) is the precursor of nitric oxide which plays an important role on pulmonary circulation and pulmonary vascular tone. Earlier studies suggested thatl -Arg levels in preterm newborns with respiratory distress syndrome (RDS) were low due to its consumption andl -Arg supplementation may reduce the severity of RDS. Our aim was detect the effect of the parenterallyl -Arg supplementation on RDS severity. The subjects were chosen between preterm newborns (gestational age <34 weeks) ( n  = 30). Twenty of the subjects were diagnosed with permaturity and RDS, and 10 of the subjects were healthy preterm newborns. Ten of the subjects was takenl -Arg (1.5 mmol/kg/d) in addition to routine RDS treatment and assumed as "Group 1". In this group, dailyl -Arg supplementation was started end of the first day, and continued at end of fifth day. The others of the subjects diagnosed with RDS was take routine RDS treatment and assumed as "Group 2". Healthy preterm newbors assumed as "Group 3". Blood collections forl -Arg levels via tandem mass spectrometry were made in first day and repeated on the seventh days. Oxygenation index was used to determine severity of RDS.l -Arg consentrations in Group 1 were 8.7 ± 4.1 μM/L and 11.9 ± 5.0 μM/L in first and seventh day, respectively.l -Arg consentrations were 12.6±4.5 μM/Land 10.9 ± 5.4 μM/L in Group 2 and 8.6 ± 5.1 μM/L and 9.4 ± 4.1 μM/L in Group 3. There is no correlation betweenl -Arg concentrations and OI also duration of the mechanical ventilation of the subjects in patient groups (Group 1 and 2).